A Novel Technique to Assess Distal Radioulnar Joint Stability Using Increasing Torque - Nilsson, Klara; Hallberg, Peter; Tesselaar, Erik; Farnebo, Simon (Journal of Wrist Surgery, 2019)
Background Previous studies on computed tomography (CT) in patients with a suspected triangular fibrocartilage complex (TFCC) injury have not been successful in assessing distal radioulnar joint (DRUJ) laxity. The aim of this study was to develop a novel servomotor-driven device for the assessment of DRUJ by applying increasing torque to the DRUJ in pronation and supination.Methods A custom-built device was designed to function during four-dimensional (4D) CT of the wrist. A torque meter, positioned between the incoming hand holder, and a direct current (DC) servomotor were used for angular positioning and for applying rotational force to the patient's arm. A total of 110 healthy participants were recruited to gather reference values for the range of motion (ROM), maximum torque in neutral and supinated/pronated position, and the ability to withstand an increasing, device-generated torque in these positions. The device was also used during 4D DRUJ CT in five patients with suspected TFCC injuries.Results A gender- and age-relevant reference chart for ROM and torque was created. Men showed a tendency (ns) toward having a larger ROM and increasing strength with increasing age, whereas women showed the opposite. Also, the dominant hand showed a tendency toward having a larger ROM and being stronger than the nondominant hand (ns). A smaller cohort of patients (n = 5) with suspected TFCC injuries showed a significantly decreased ability to withstand increasing torque in both supination (2.1 ± 0.3 vs. 3.1 ± 0.2 s; p < 0.005) and pronation (2.3 ± 0.5 vs. 3.1 ± 0.4 s; p < 0.0005) and also showed a clear laxity on real-time 4D CT image sequences. Decreased strength at all positions was also found (average 74% decrease compared to noninjured side).Conclusion Reference values for torque strength and ability to withstand increasing torque can be used clinically in the assessment of patients with symptoms that could represent ligamentous injuries to the TFCC. The ability to use the device during CT enables radiographic evaluation of instability during increasing torque.Level of Evidence This is a Level II study.
Keywords: DRUJ Instability; TFCC injury; 4D CT; torque